2022
DOI: 10.3389/fonc.2022.947188
|View full text |Cite
|
Sign up to set email alerts
|

The Link Between the Microbiota and HER2+ Breast Cancer: The New Challenge of Precision Medicine

Abstract: The microbiota is emerging as a key player in cancer due to its involvement in several host physiological functions, including digestion, development of the immune system, and modulation of endocrine function. Moreover, its participation in the efficacy of anticancer treatments has been well described. For instance, the involvement of the breast microbiota in breast cancer (BC) development and progression has gained ground in the past several years. In this review, we report and discuss new findings on the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 129 publications
0
9
0
2
Order By: Relevance
“…It has been shown that the constitution of the microbiota influences tumour biology, such as oncogenic signalling, drug metabolism, or immune system regulation. All these aspects will contribute to the cancer development, growth, and treatment response [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the constitution of the microbiota influences tumour biology, such as oncogenic signalling, drug metabolism, or immune system regulation. All these aspects will contribute to the cancer development, growth, and treatment response [16].…”
Section: Introductionmentioning
confidence: 99%
“…Trastuzumab, a HER2 targeted therapy, prevents HER2 receptor dimerization and activates the innate immune response 47 . However, differences in gut microbiota brought about by usage of antibiotics impact the activation of the innate immune response, thus affecting the efficacy of trastuzumab therapy 27,48 . Studies have thus demonstrated the active role of microbiota in trastuzumab response, and modulation of this microbiome may facilitate better treatment response.…”
Section: Microbiome and Breast Cancermentioning
confidence: 99%
“…Прогноз раннего РМЖ зависит от параметров клеточной автономии и иммунитета. Влияние кишечного микробиома на клинический исход раннего РМЖ был впервые оценен S. [6].…”
Section: связь с клинико-морфологическими параметрами лечением и исхо...unclassified
“…Количество исследований, посвященных различиям между микробиотой кишечника больных РМЖ и здоровых женщин, значительно увеличивается [3][4][5][6]. Среди симбиотических микробных популяций человека наиболее тщательно изучены и охарактеризованы бактерии, обитающие в кишечнике.…”
Section: Introductionunclassified